Systemic Risk Management in Small Manufacturing Networks - Radhitya, Zaky (Journal of Sustainability Industrial Engineering and Management System, 2024)
In an increasingly volatile industrial landscape, the management of systemic risk has become a critical concern, particularly for small manufacturing networks (SMNs) composed predominantly of interconnected small and medium-sized enterprises (SMEs). These networks are vulnerable to cascading disruptions due to structural interdependencies, limited redundancy, and constrained institutional support. This study aims to investigate the nature of systemic risk in SMNs, assess existing mitigation strategies, and explore the role of collaboration and digital innovation in enhancing resilience. Employing a qualitative research methodology based on literature review, the study synthesizes insights from 65 peer-reviewed academic sources published between 2010 and 2024. The research is structured around four analytical themes: the triggers of systemic risk, current mitigation practices, network-based collaboration, and the impact of digitalization and policy innovation. The findings reveal that while SMNs have developed adaptive mechanisms such as supplier diversification and lean production buffers, these remain insufficient without coordinated inter-firm governance and technological integration. The study also highlights the paradoxical role of digital tools, which both mitigate and introduce new systemic risks, especially in resource-constrained environments. Furthermore, institutional frameworks and collaborative governance structures are identified as key enablers of systemic resilience. The study contributes theoretically by expanding the discourse on systems thinking and resilience engineering within SME networks and offers managerial implications for embedding risk management into digital and relational infrastructures. The conclusions advocate for targeted policies, inclusive platforms, and training programs to co-create resilient, adaptive, and sustainable manufacturing ecosystems.